Edukasi Penanganan Cedera melalui Metode Stretching dan Strengthening dalam Fisioterapi pada Anak-Anak Indonesia di Malaysia - Mianti Nurrizky Sutejo; Sesilia Elsina Keisha (Jurnal Pengabdian Masyarakat Mentari, 2026)
This community service activity aims to improve the knowledge of Indonesian children in Malaysia regarding the management of minor injuries through stretching and strengthening methods in physical therapy. The activity was conducted in April 2026 with participants aged 5–17 years. The implementation method consisted of an opening session, a pre-test, presentation of the material, role-playing, a post-test, and a closing session. The material was presented using PowerPoint slides in language easily understood by the participants. Additionally, a role-play was conducted on managing knee injuries resulting from playing soccer to enhance practical understanding. The introduced exercise techniques included hamstring stretches, quadriceps stretches, straight leg raises, mini squats, and bridge exercises. The results of the activity showed that the participants were very enthusiastic about the session, actively asked questions, and were able to understand the importance of stretching and muscle strengthening in the prevention and initial management of injuries. The educational method, which combined material delivery with role-playing, was deemed effective in improving children’s understanding of physical therapy and the management of minor injuries. It is hoped that this activity can serve as an engaging and beneficial health education tool for Indonesian children living abroad